Climate and Energy Governance for the UK Low Carbon Transition The Climate Change Act 2008 - Muinzer, Thomas L. (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
The UK Climate Change Act was the first case of a country implementing blanket legally binding long-term emissions reduction targets in order to combat climate change. This book provides the first accessible and in-depth analysis of the UK's complex Climate Change Act framework, presenting the discussion in a clear and interdisciplinary manner designed to open the workings of the challenging framework to a broad audience. It discusses the political 'story' surrounding the framework, and its treatment in scholarly environmental literature; analyses the technical content of the Act; explores the framework's international significance, and its internal 'subnational' dimensions and impact, engaging the UK's devolved jurisdictions of Northern Ireland, Scotland, and Wales. This first, much-needed interdisciplinary treatment of the framework is both introductory and analytical in nature and will be of interest to scholars, practitioners and general readers of environmental studies, policy and governance. .